2015
DOI: 10.3892/ijmm.2015.2222
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 induces EMT by the transactivation of epidermal growth factor signaling through HA/CD44 in lung and breast cancer cells

Abstract: Epithelial-mesenchymal transition (EMT), a process closely related to tumor development, is regulated by a variety of signaling pathways and growth factors, such as transforming growth factor-β1 (TGF-β1) and epidermal growth factor (EGF). Hyaluronan (HA) has been shown to induce EMT through either TGF-β1 or EGF signaling and to be a regulator of the crosstalk between these two pathways in fibroblasts. In this study, in order to clarify whether HA has the same effect in tumor cells, we utilized the lung cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 38 publications
6
67
1
2
Order By: Relevance
“…The TGF-β1-induced EMT and increased invasion in various types of cancers has previously been suggested [36]. In this study, we found a FASN-TGFβ1-FASN positive feedback loop in cisplatin-resistant lung cancer cells, but not in parental cells.…”
Section: Discussionsupporting
confidence: 66%
“…The TGF-β1-induced EMT and increased invasion in various types of cancers has previously been suggested [36]. In this study, we found a FASN-TGFβ1-FASN positive feedback loop in cisplatin-resistant lung cancer cells, but not in parental cells.…”
Section: Discussionsupporting
confidence: 66%
“…Such examples are the Notch receptors, 43 the insulin-like growth factor I receptor 44 and the CD44 receptor, which is also an established marker for BCSC. 45 Interestingly, and although EGFR overexpression is associated with breast cancer cell proliferation and invasion, 46 Kari et al 47 reported that malignant tumor cells faced with inadequate cell-matrix contacts, critically depend on EGFR activation for survival. Taking into account that mAb4C5 significantly inhibits the growth of MDA-MB-231 and mammosphere tumors, we next examined the possible therapeutic effect of this antibody on palpable tumors derived from mammospheres, taking into consideration that this subpopulation is greatly enriched in cells with the CD44 C /CD24 ¡/ low BCSC phenotype and additionally over-expresses eHSP90.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is involved in various functions and leads to the dissociation of cell-cell adhesions, disappearance of apical-basolateral polarity, reorganization of spindle-cell shape, promotion of cell motility, and acquisition of mesenchymal markers [2] . It is well known that transforming growth factor-β (TGF-β) is a major inducer of EMT in cancer cells during tumor progression [3] . Tumor necrosis factor-α (TNF-α) is able to accelerate the EMT process induced by TGF-β [4] .…”
Section: Introductionmentioning
confidence: 99%